London: A Book of Opposites - Evanson, Ashley (Hello World, 2015)
Hello, World is an exciting board book series that pairs early learning concepts with colorful, stylish illustrations of cities around the world. London can be rainy, or it can be sunny. Some of the buildings are very old, while others are quite new. Explore opposites through the sights of London in this gorgeous board book!